2007
DOI: 10.1007/s00383-007-1983-x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental anomalies of the enteric nervous system in normoganglionic segments of bowel from rats with total colonic aganglionosis

Abstract: Polysialyated neural cell adhesion molecule (PSA-NCAM) is a marker for immature neurons and S100 beta is a known marker for enteric glia. The aim of this study was to determine the maturation of the enteric nervous system (ENS) in normoganglionic (Ng) bowel from rats with total colonic aganglionosis (TCA). Ng ileum was obtained from TCA rats (spotting lethal: mutant, sl/sl: n = 15) at 10, 19, and 24 days of age (n = 5 for each age). Normal control Ng ileum was obtained from wild type littermates (+/+, n = 25) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Many of the HSCR animal models (particularly those with TCA) demonstrate an extended transition zone or region of hypoganglionosis. 51 TCA along with a long hypoganglionic transition zone has been reported in the Dominant megaco- lon mouse (Dom) 52 as well as the murine-16 animal model of down syndrome associated Hirschsprungs disease. 53 The long hypoganglionic segment with increased immaturity of cells reported in some animal models, 51 has not been confirmed in humans (although suspected).…”
Section: An Extended Transition Zone In Tca?mentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the HSCR animal models (particularly those with TCA) demonstrate an extended transition zone or region of hypoganglionosis. 51 TCA along with a long hypoganglionic transition zone has been reported in the Dominant megaco- lon mouse (Dom) 52 as well as the murine-16 animal model of down syndrome associated Hirschsprungs disease. 53 The long hypoganglionic segment with increased immaturity of cells reported in some animal models, 51 has not been confirmed in humans (although suspected).…”
Section: An Extended Transition Zone In Tca?mentioning
confidence: 99%
“…A number of developmental conditions have been associated with TCA, 51 along with several known syndromes inherited in an autosomal-dominant manner. Although the pattern of conditions associated with HSCR has already been of great value in revealing many of the genetic natures and associations of the disease, 54,55 there appears to be no consistent association with specific anomalies and TCA.…”
Section: Associated Congenital Anomalies and Tcamentioning
confidence: 99%
“…The case presented here adds to the complexity in our incomplete understanding of intestinal aganglionosis and its etiology. Murine models have demonstrated long hypoganglionic segments with increased immaturity of cells [6, 11]. Watanabe et al described hypoganglionosis as a completely different clinical entity from HD in which there is no clear identification of a transitional zone [12].…”
Section: Discussionmentioning
confidence: 99%
“…Polysialylated neural cell adhesion molecule is also believed to play an inhibitory role in cell-cell interactions [9][10][11] and also to have a negative regulatory effect on neuromuscular junction synaptogenesis in the chick ciliary ganglion system [12]. Previously, we studied PSA-NCAM immunoreactivity for investigating bowel neuronal maturation and found that in normal rats, neurons mature before day 19 [8]. In this study using human specimens, PSA-NCAM immunoreactivity was significantly decreased after 1 year in the control group, suggesting that enteric neurons are already mature in humans after 1 year.…”
Section: Discussionmentioning
confidence: 97%
“…Most work with PSA-NCAM has been conducted on rat central nervous system, but recently, we reported that neurons in normoganglionic (Ng) segments from rats with total colonic aganglionosis remain immature beyond an age when they should be mature [8] by following the maturation of neurons according to age using immunohistochemistry.…”
mentioning
confidence: 98%